Eksplorasi Faktor Infrastruktur, Beban Kurir, dan Kemacetan di Jalan terhadap Pengiriman Paket di Kota Purwakarta - Muhammad Abdul Isra Kurniawan; Muhammad Zaki Balapradhana Heryana; Zacky Hendra Prawira Hendrawan (CV. ALIM'SPUBLISHING, 2026)
This study aims to identify the underlying factors associated with package delivery in Purwakarta City, particularly those related to infrastructure, courier workload, and road traffic congestion. Package delivery is an important aspect in supporting distribution activities and logistics services; therefore, the smoothness of the delivery process is a crucial factor in determining customer satisfaction. However, in practice, various obstacles still frequently occur and have the potential to hinder timeliness and the quality of delivery services. This study uses an exploratory approach with factor analysis methods to identify the dominant variables affecting the package delivery process. Data were collected through observations, questionnaires, and/or interviews with parties involved in package delivery activities in Purwakarta City. The results of this study are expected to provide an overview of the most influential factors affecting the effectiveness of package delivery, as well as serve as a basis for delivery service companies in developing service improvement strategies. Thus, this study is expected to make a practical contribution to improving the efficiency of package distribution in the Purwakarta City area.